PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII - Arzi, Ghina Haifa (Departemen Matematika, 2023)
This study was conducted to acquire the ability of mathematical problem solving of student in mathematics, the part of learning mathematics, conducted at SMPN 1 Batusangkar. The result of the first test of math problem-solving skills was that the student did not solve the problem well. One solution to overcome this is the application of problem-based learning models. The research results shown that mathematical problem-solving skills who learn to use problem-based learning outperform those who learn to use direct learning. Initial tests of mathematics problem-solving ability shown that the students did not solve the problem well. One attempt to overcome this is the use model of problem-based learning. The research result shown that those who learn to use problem-based learning have better problem-solving skills in mathematics than those who learn to use direct learning. Keywords. – Problem Based Learning, The Ability of Mathematical Problem Solving